Concept of Restorative Justice in Criminal Acts of Sexual Violence with Child Perpetrator and Victims - Nani Susilowati; Nurini Aprilianda; Faizin Sulistio (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
This article aims to clarify the idea of restorative justice in situations of sexual violence where children are both the perpetrator and the victim. This study uses normative legal research with a statute and conceptual approaches. The results show that law enforcement against children as perpetrators of crimes of sexual violence with child victims must still pay attention to the principle of proportionality. This principle seeks to limit punitive consequences and restrain public responses so that they stay proportionate to juvenile perpetrators of sexual violence. In addition to focusing on activities, this idea also considers the child's environment. In the meantime, law enforcement that cannot be conducted through diversion must nevertheless regard the rights of the child, so that when children are criminalized, only half of the adult punishment is imposed, so that they can return to society appropriately and be equipped with skills.